ANALISA PRINSIP PROXIMITY DAN SIMILARITY PADA KHAT DIWANI JALY KARYA HAMID AYTAC - Amrulloh, Ahmad Yasir; Ato’illah, Ato’illah (Jurnal Kajian Seni, 2024)
The elements of proximity and similarity was basic principles in typographic design. So far, these elements have only been used on objects such as logos, animations, monuments, and graphic designs. Meanwhile, the study of artwork in the form of Arabic calligraphy is still very minimal, even though it also has these elements. This study aim to identify these elements in a piece of Yusuf surah: 101 written by Turkish calligrapher, Hamid Aytac in the Diwani Jaly khat type written in 1348 AH. This work has become a reference for calligraphy students today. This research uses a descriptive qualitative method, data sources are documents of calligraphy works written, then analyzed using gestalt theory in the form of proximity and similarity elements. The results showed that Hamid's work contains elements of proximity and similarity. The element of proximity is found in the writing of letters in the work that are close together in a balanced manner. The similarity element is found in the hollow of the letter ba' from the sentence rabbi which has a similar shape to the letter kaf from the sentence al-mulk, the letter tsa from the sentence al-ahadits, the letter ta' from the sentence al-samawat and the letter nun from the sentence anta. Then, the concavity of the letter ya' of the sentence ataitani has similarities with the letter ya' of the sentence allamtani. The nun of the sentence min is similar to the lam of the sentence ta'wil. While at the end of the verse, the similarity element is found in the letters wawu, ya’ and nun in the sentence tawaffani musliman wa alhiqni bi al-shalihin. This finding shows that Hamid's work has aesthetic value based on the typographic perspective in the form of the principles of proximity close edge and shape similarity.